WILL THE COVID-19 PANDEMIC CHANGE ANYTHING? – A VIEW FROM THE ANGLE OF EXPERTS IN MICROBIOLOGY - Delic, Snezana (HEALTH CARE, 2020)
The COVID-19 pandemic has shaken the majority of health systems around the world, pointing out that it is necessary to invest in the modern equipment for molecular diagnostics, as well as to provide an adequate space within microbiological laboratories for this form of diagnostics, according to the standards that are required for such procedures. It is also necessary to increase the number of specialists within the field of medical microbiology, especially in those laboratories where the lack of experts is at an alarming level. Investing in the diagnostic branches of medicine (and microbiology, as well) provides the optimal health protection: fast and correct diagnosis, the application of the adequate antimicrobial therapy as soon as possible, resulting in greater chances for curing. Furthermore, this leads to fewer hospital days and fewer deathly outcomes, while for infirmary patients this means a faster diagnostic procedure and a decrease in the number of specialist examinations, which are sometimes unnecessary. During the Covid-19 pandemic, The Section of Microbiologists of the Serbian Medical Society as well as the Institute for Microbiology and Immunology of the Faculty of Medicine of Belgrade University, have made themselves available to the Ministry of Health of The Republic of Serbia for the identification of potential laboratory capacities and for conducting necessary experts training, for doctors specialists and for laboratory technicians, as well. Although new technologies develop fast and the laboratory work becomes automated, in theory and in practice as well, an educated expert in medical microbiology still presents the main pillar that stands up for a precise, modern, quick and high-quality diagnosis of infective pathogens, especially those with pandemic potential.